(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Tax fraud is a very large problem within the economies of Latin America and Ecuador, it is no exception; the northern commercial sector of the city of Guayaquil was located as the object of study, which presents a problem with a limited current income due to tax fraud, raising as main objective: to characterize the relationship between corporate tax fraud and public current income in the period 2018-2020. The research design is qualitative. The interview technique was used and applied to ten experts chosen for convenience. The results show that tax evasion is an evasion mechanism that directly affects current revenue and affects the funds available to the State to improve strategic sectors for the benefit of society in general. It is concluded that the general objective was met, recommending that there should be greater tax control by the competent national body and studies should be conducted to help estimate efficient calculation mechanisms for tax evasion and money laundering that affect the economy of Guayaquil.